Watt-class continuous wave Er3+/Yb3+ fiber amplifier - Ebbeni, May (Kansas State University, 2011)
Rare-earth doped optical fibers can be used to make optical amplifiers in the near infrared with large optical gain in an all fiber based system. Indeed, erbium doped fibers made gain possible within the 1532 to 1560 nm band which makes long span fiber optical communication systems a possibility. Erbium doped fibers have also been used to make narrow linewidth or mode-locked lasers. Other rare-earth doped fibers can be used for amplifiers in other near-infrared spectral regions. Recently, fiber amplifier technology has been pushed to produce watt level outputs for high power applications such as laser machining. These high power amplifiers make new experiments in ultrafast fiber optics a possibility. This report reviews the current literature on Watt-class continuous wave erbium doped amplifiers and discussed our attempt to develop a high power Yb/Er amplifier. After the design of the cladding pump in 1999, the world’s first single mode fiber laser with a power greater than 100 Watts of the continuous wave light was introduced. After 2002 there was a huge spike in the output powers (up to 2 kW) of lasers based on rare-earth doped fibers. Our own work involved developing a 10 W amplifier at 1532 nm and 1560 nm. A high power amplifier was made by seeding a dual-clad Yb/Er co-doped fiber pumped at 925 nm using a lower power erbium doped fiber amplifier. We will discuss the design and construction of the amplifier, including the technical difficulties for making such an amplifier.
Keywords: Power amplifier; Er/Yb doped fiber; Physics (0605)